Effects of remote combine exercise-music training on physical and cognitive performance in patients with Alzheimer’s disease: a randomized controlled trial - Shokri, Ghazaleh; Mohammadian, Fatemeh; Noroozian, Maryam; Amani-Shalamzari, Sadegh; Suzuki, Katsuhiko (Frontiers in Aging Neuroscience, 2024)
This study aimed to investigate the effects of combined remote music and exercise training on the cognitive, psychological, and physical function of patients with Alzheimer's disease (AD). Fortyone AD patients were randomly allocated to three groups, including control (C), training (T), and training with music (TM) groups. Participants were evaluated by cognitive and performance test batteries before and after the interventions. Both experimental groups performed 36 remote workouts in three months online via WhatsApp video call individually with the trainer. Training included simple and varied movements of all physical indicators. The number of sets began withtwo sets and progressively increased to one set every month, 5-10 repetitions per set. The overload was applied by reducing the break between sets every week. The TM group performed the same exercises while listening to Mozart and traditional Iranian songs. We observed a significant main, group, time, and interaction effect on Romberg (ηp 2 :0.72), 30-second chair sit and stand (ηp 2 :0.75), and walking on steppe test (ηp 2 :0.63). Furthermore, there was a significant main time and interaction effect on push-ups (ηp 2 :0.43), sit and reach (ηp 2 :0.64), and MMSE (ηp 2 :0.76). In all variables, two experimental groups demonstrated substantial improvements than the C group (p<0.01). In addition, the TM group (27.8%) showed a significant improvement compared to the C group (-6.4%) and the T group (12.2%) in MMSE. Combined remote training with listening to music as adjuvant treatment is an appropriate item to improve the cognitive and physical performance of Alzheimer's patients, especially during the COVID-19 pandemic.